IDENTIFIKASI WASTE DENGAN MENERAPKAN METODE BORDA DAN ROOT CAUSE ANALYSIS PADA PROYEK KONSTRUKSI - Nabilah, Veren Nurlin; S, Setiono; Setyawan, Ary (Jurnal Riset Rekayasa Sipil, 2025)
One of the factors contributing to Indonesia’s high annual construction activity is the building of high-rise structures. However, every building project can potentially create several issues that lead to waste. Lean construction which aims to reduce waste and increase value, was therefore used. Waste is any type of loss from an activity that produces expenses either directly or indirectly but does not result in a product’s value or benefits. The purpose of this study is to determine the most common types of garbage and examine the factors that contribute to it. This research will include a review to identify the variables that contribute to waste and factors that cause it, as well as a root cause analysis using the 5-why’s method. According to the computation’s findings, the most common waste variables and their causing factors were 179 points for defects and careless supervision, 155 points for overprocessing and a factor for misunderstandings brought on by design modifications, and 145 points for overproduction and factor related to a lack of control material production. Defects are the main cause of waste because they prevent cost overruns, overprocessing because of a lack of resources for creating new design drawings, and overproduction because the planning and production implementation teams in the field do not coordinate.